UPAYA GURU DALAM MENANAMKAN NILAI KEAGAMAAN PADA ANAK BERKEBUTUHAN KHUSUS DI SLB MA’ARIF NU LAMONGAN - Nabilah, Faiqotin; Jasminto; Ridhwan, Burhanuddin (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam, Universitas Hasyim Asy'ari Tebuireng Jombang, Indonesia, 2024)
Initially the term special needs emerged from special education given to students who experienced physical or psychological disabilities. There are 4 basic principles of children's rights contained in the Convention on the Rights of the Child which was approved by the United Nations General Assembly on 20 November 1989 and ratified by Indonesia in 1990, namely Non-Discrimination, the Right to live, the Right to develop and the Right to to have an opinion. Learning for children with special needs requires an individualistic approach. Based on the problems above, this research has 3 research focuses: 1) What are the religiousvalues instilled in children with special needs at SLB Ma'arif NU Lamongan? 2) How do Class Teachers Efforts to Instill Religious Values in Children with Special Needs at SLB Ma'arif NU Lamongan? 3) What are the Supporting and Inhibiting Factors in theImplementation of Instilling Religious Values in Children with Special Needs at SLB Ma'arif NU Lamongan? In this research, researchers took a qualitative research method approach. In this research, the researcher took a qualitative descriptive type of research. Data collection was carried out using interviews, observation and documentation.